A comunidade de plantas com nectários extraflorais em uma savana brasileira: morfologia, fenologia e a fauna associada - Pires, Marcela Saldanha (2015)
Extrafloral nectaries (EFNs) are nectar-secreting glands found in various taxa of plants. These structures can attract different groups of animals which use the extrafloral nectar as a food source. Considering EFNs are structures commonly observed in the Brazilian Cerrado, the aim of this study was to identify the plant community (trees, lianas and scrub) bearing EFNs in an area of Cerrado. We also characterized morphological types of nectaries, location, phenology, productivity and arthropods that feed on extrafloral nectar. Twenty transects were established in order to survey the species. The species bearing EFNs were identified and characterized for its location and morphology each fifteen days and accompanied to evaluate its phenology over a year. Samples of extrafloral nectar and arthropods were held in different plant species. We recorded 26 species of EFN-bearing plants, distributed among trees, shrubs and lianas. The EFNs were found in different parts of plants, including vegetative and reproductive structures, or species that had the glands on both locations. Duo to the phenology aspects, we observed a pattern in which the majority of species presented secretory activity of EFNs in September and October, matching with the end of the dry season and the beginning of the rainy season. Thus, the strong seasonality in the Cerrado may be an important factor influencing these glands activities. The sugar concentration of nectar differed between species (H= 52.329; p<0.001). Were observed 35 species of arthropod in the EFN foraging, being Hymenoptera (Formicidae) the most representative group with 25 species, followed by Araneae and Coleoptera with three species each, Diptera one species and Hemiptera with two species. The study showed that EFN structures are common to different plant strata of the Cerrado, and also highlights the first record of EFN for the species Bionia coriacea (Fabaceae) and Smilax polyantha (Smilacaceae). The EFN have distinct morphologies and its secretory activity is concentrated in specific periods of the year. A variety of arthropods use extrafloral nectar as food source and, thus, plants with EFN can have great influence on the structure of communities in the Cerrado.